Akibat Hukum Budaya Kad’di Dalam Adat Masyarakat Sabu - Chatryen M Dju Bire; Herman Elfridus Seran; Jenny Ermalinda (PMIH Untag Semarang, 2023)
In relation to marital problems, if an incident occurs where the husband dies first, the culture of Kad'di must be applied. Culture is Kad'di carried out when the husband dies where the husband's body has been buried. When the wife returns to her original clan, important things arise, including the management of children and property problems. Likewise, if the children left behind are immature, problems will arise, namely who or which party is responsible for guiding and caring for them. Then in relation to the issue of marital property. This is what makes researchers interested in conducting research with the title